2021
DOI: 10.24018/ejbmr.2021.6.1.714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intellectual Capital on Organizational Sustainability with Employee Innovative Behavior as Intervening Variables in Pt. Jaya Maritime Services

Abstract: Organizational sustainability is an important strategy to increase organizational capabilities not only to provide economic benefits, but also social and environmental benefits. The reality on the ground is that not all companies really pay attention to the dimensions of sustainability, both in terms of economy / profit, people and the environment. This is because it is considered that the sustainability of the organization is voluntary. Therefore, research is needed on the factors that influence organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…So, Structural Capital which includes employee responsibility to the company through innovative behavior of employees in terms of generating new ideas becomes the most important part in fulfilling organizational performance, especially from the learning and growth perspective. This is in line with the study conducted by Najib & Nawangsari (2021), that the company's Structural Capital is an important factor in organizational success and the company's ability to maintain competitive advantage through employee innovative behavior.…”
Section: The Effect Of Structural Capital On Organizational Performan...supporting
confidence: 90%
See 1 more Smart Citation
“…So, Structural Capital which includes employee responsibility to the company through innovative behavior of employees in terms of generating new ideas becomes the most important part in fulfilling organizational performance, especially from the learning and growth perspective. This is in line with the study conducted by Najib & Nawangsari (2021), that the company's Structural Capital is an important factor in organizational success and the company's ability to maintain competitive advantage through employee innovative behavior.…”
Section: The Effect Of Structural Capital On Organizational Performan...supporting
confidence: 90%
“…Intellectual Capital is a very important aspect for employees and companies because it can maximally create value-added and competitive advantage, which in turn will affect organizational sustainability (Arshad et al, 2016;Omar et al, 2017;Yusoff et al, 2019). The innovative behavior of employees is also an important determinant of organizational success and the company's ability to maintain a competitive advantage (Najib & Nawangsari, 2021). Intellectual Capital as investment value in the form of abilities, knowledge, ideas, ideas, creativity, innovation, effort, and commitment in the work and social environment to carry out their duties so as to create value to improve organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…6.20%, 6.77%, and 0.77% gains are observed in fisheries output if intellectual capital rights rise by 1% in the case of FEOLS, FMOLS, and DOLS, respectively. This conclusion was verified by Nurlita et al (2021), Najib and Nawangsari (2021), and Li et al (2021) for developing nations, Alsaleh and Abdul‐Rahim (2022a, 2022b) for EU developing countries which suggest that intellectual capital rights enhance fisheries productivity. The conclusion reveals that economic expansion positively and substantially impacts fisheries sustainability in EU13 developing nations.…”
Section: Resultsmentioning
confidence: 69%
“…In the Mediterranean Sea, Yıldırım et al (2022) and Seisay (2022) looked into the relationship between intellectual capital developments and fisheries footprint, and they concluded that a relatively low level of intellectual capital rights harms the sustainability of fisheries, while a relatively high level has a positive impact. It was examined in Indonesia by Nurlita et al (2021) and Najib and Nawangsari (2021), who also proposed a complete and cohesive plan and coordinated and harmonized policies for the sustainability of the blue economy. According to Climent‐Pérez et al (2023), and Schrobback et al (2022), sustainable fisheries refer to the marketing and distribution of fish products through aquaculture or wild catch in ways that would not harm the long‐term sustainability of species while also securing the future of the marine ecosystem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Farooq et al (2019) suggested that a selection of differing cross-cultural management styles involving the change of management and welfare system, changing staff morale, and different business performance is the reason why cross-cultural management in multinational corporations is faced by corporate identity challenges for its employees following the transition (Farooq et al, 2019). Based on this, this study has developed a research hypothesis aimed at verifying the mediating effects of cross-cultural management and multinational corporate employee cultural identity based on the relationship among the variables (Najib and Nawangsari, 2021).…”
Section: Methodsmentioning
confidence: 99%